Transformação da p-sinefrina no fígado e seus efeitos sobre o metabolismo hepático de ácidos graxos e sobre os níveis sanguíneos de glicose e ácidos graxos - Silva-Pereira, Juliany Fontoura (2016)
Citrus aurantium (bitter orange) extracts have been used in products that allegedly can induce weight loss. Several alkaloids with adrenergic activity have been found in C. aurantium, such as p-synephrine and p-octopamine. The alkaloids p-synephrine and p-octopamine present structural similarities to endogenous neurotransmitters and ephedrine. A lipolytic activity of p-synephrine and p-octopamine has been found in both rat and human adipocytes. In this respect p-synephrine is more active in rat than in human adipocytes. Studies have also shown that p-synephrine and p-octopamine are able to induce many modifications in both metabolism and hemodynamics in the perfused rat liver. The modifications include stimulations of glycogenolysis, glycolysis, gluconeogenesis and oxygen consumption. Similar stimulations were found when the aqueous extract of C. aurantium was infused. The bioavailability of orally ingested p-synephrine depends on the rate of absorption in the gastrointestinal tract but also on the rate by which the compound is transformed in the liver, the first organ that receives the compound via the portal vein. The biotransformation of p-synephrine and p-octopamine is not as well known as that of other adrenergic amines such as epinephrine and norepinephrine, but it is known that gastric absorption is complete. In the present work, the transformation of p-synephrine and p-octopamine was investigated in the isolated perfused liver in which arterio-venous differences can be accurately measured. It is hoped that valuable and still lacking information about the biotransformation of p-synephrine and p-octopamine can be obtained. Special attention was devoted to the single pass extraction of each compound as well as to the kinetics of uptake. For comparative purposes the transformation of epinephrine and norepinephrine was also measured. In addition to this, two important questions related to the actions of p-synephrine and p-octopamine were investigated. One of these questions was if these compounds also exert lipolytic activity in the liver. The other question was if the lipolytic and glycogenolytic effects of these amines that were detected in vitro can be demonstrated to occur in vivo.